Integration of Design of Experiments, Analysis of Variance and Response Surface Methodology in Assessing Heterogeneous Catalysts Processes: A Minireview - Carlos Esteban Aristizábal‐Alzate; Eva Castillejos‐López; Ana Belén Dongil; Manuel Romero‐Sáez (ChemistryOpen)
Abstract This work reviews the application of Analysis of Variance (ANOVA), Design of Experiments (DOE), and Response Surface Methodology (RSM) in heterogeneous catalysis, based on an analysis of recent scientific literature. Heterogeneous catalysis plays a key role in various industries, guiding chemical reactions, optimizing the performance of different processes and/or prioritizing products, and ANOVA, DOE and RSM are valuable tools to understand the intricate relationships between catalyst properties, process variables and reaction responses. This understanding facilitates improvements in catalysts performance and selectivity, thereby optimizing processes. Drawing insights from recent studies, this minireview highlights the different applications of ANOVA‐based experimental designs and RSM optimization techniques in catalytic process evaluation. Therefore, this review provides valuable insights into these current statistical methodologies applied to heterogeneous catalysis research, informing the relevance and future directions of the research in the field.